Quantum phase transitions and thermodynamics of quantum antiferromagnets with competing interactions - Trippe, Christian; Klümper, Andreas (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We study the isotropic Heisenberg chain with nearest and next-nearest neighbor interactions. The ground state phase diagram is constructed in dependence on the additional interactions and an external magnetic field. The thermodynamics is studied by use of finite sets of nonlinear integral equations resulting from integrability. The equations are solved numerically and analytically in suitable limiting cases. We find second and first order transition lines. The exponents of the low-temperature asymptotics at the phase transitions are determined.